Learning from lived experience in government care: sharing gains in knowledge and practice in youth participation with key care stakeholders - Jade Purtell; Luke Westwick; Brittany Witnish; Jarrad Butcher; Annie; Ralph Salera; Jenna Bollinger (Scottish Journal of Residential Child Care)
Increasingly progressive organisations are changing how they see and work with young people. Such organisations as well as government are acknowledging the invaluable skills and insights young people with lived experiences can contribute as youth leaders, and genuine co-design partners shaping policy with key decision makers. This paper presents three care experienced perspectives on the benefits and challenges of capturing the voices of young people to inform policy and organisational decision-making in youth services. Sharing models of effective youth participation in policy development may lead to improved policy making and greater efficiency in child welfare service delivery. Encouraging young people's participation and empowerment involves a range of 'soft skills' that can be resource and time intensive. Sharing learning and knowledge from and about this work can be difficult as a result. The authors work on many innovative and important youth participation projects and seek to share young people's suggestions for how to facilitate meaningful participation for young people. Strategies for avoiding tokenism and increasing shared decision-making are discussed.